Análise dos atendimentos obstétricos realizados pelo SAMU de Botucatu, SP - Michelin, Nathallia Seródio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The general objective of the present study was to analyze the calls from the obstetric users of SAMU 192 in Botucatu, in 2012, as regards their pertinence and taking the women's parity into consideration. The present analytic and observational study included a population of women in the pregnancy-puerperium cycle as well as professionals of the primary healthcare network in the city of Botucatu, SP, Brazil. Data were collected from records of the Service and pertinent calls were all those resulting in referrals to hospitals and classified as red, orange and yellow according to the risk criteria proposed by the Brazilian Ministry of Health. As regards the involved professionals, the study sample comprised 67 peoples including physicians, nurses, nursing assistants/technicians and community healthcare agents. The chi-square, Kruskal-Wallis and exact Fisher's tests were utilized in the statistical analyses, and the critic p value was set at <0.05. The analyses were performed with the SPSS v15.0 software. The present study was approved by the Committee for Ethics in Research of Faculdade de Medicina de Botucatu - UNESP. A low prevalence of non pertinent demand was observed as both classification criteria were considered. No statistically significant difference was observed in relation to the non pertinent demand as the women's parity was considered. As the different professional categories involved in primary healthcare activities were considered, no difference was observed in the degree of priority given by SAMU to primiparae and multiparae. The scoring of the professionals' knowledge about demand pertinence ranged between 7 and 8 and may be considered high. The excellent health conditions of the women at their admission, their mild complaints and the reporting of mild findings by the professionals suggest that the index of referrals to the reference center might be overestimated, indicating lack of integration between primary ...

O objetivo geral do presente estudo foi analisar os chamados da população obstétrica usuária do SAMU 192 de Botucatu no ano de 2012 com relação à sua pertinência, considerando a paridade das mulheres. Trata-se de estudo observacional e analítico, realizado com população de mulheres no ciclo gravídico/puerperal e com profissionais da rede básica de saúde do município de Botucatu-SP. Os dados foram coletados a partir das fichas de atendimento do Serviço e chamados pertinentes foram todos os que resultaram em encaminhamento ao hospital e quando classificados nas cores vermelha, laranja e amarela, segundo critério de risco proposto pelo Ministério da Saúde. Quanto aos profissionais, a amostra foi composta por 67 pessoas, entre médicos, enfermeiros, auxiliares/técnicos de enfermagem e agentes comunitários de saúde. Nas análises estatísticas foram utilizados o teste qui-quadrado, Kruskal-Wallis e exato de Fisher, sendo que em todos os casos considerou-se p crítico <0,05. As análises foram feitas com o software SPSS v15.0. Este estudo foi aprovado por Comitê de Ética em Pesquisa da Faculdade de Medicina de Botucatu - UNESP. Para ambos os critérios de classificação utilizados, a prevalência de demanda não pertinente foi baixa. Não houve diferença estatisticamente significativa na demanda não pertinente segundo a paridade. Quando se consideram as diferentes categorias profissionais que atuam na atenção básica, não houve diferença entre elas, quando se investigou se primíparas devem ser prioritárias para o SAMU, quando comparadas às multíparas. O escore de conhecimento sobre a pertinência da demanda ao SAMU obtido pelos profissionais variou entre 7 e 8 e pode ser considerado elevado. A excelente condição da mulher no atendimento, as queixas brandas e o registro de achados leves pelos profissionais sugerem que o encaminhamento ao serviço de referência pode estar sendo superestimado, indicando falta de...
Keywords: Enfermagem obstetrica; Enfermagem de emergencia; Serviços médicos de emergência; Emergency medical services; Obstetrical nursing